Física e arte: uma análise de dissertações e produtos do Mestrado Nacional Profissional em Ensino de Física - Gerlach, Jennifer Schroder (Universidade Federal de São Carlos, 2025)
This study aimed to investigate interdisciplinary approaches between physics and art in dissertationsand educational products from the National Professional Master’s Program in Physics Teaching (MNPEF). The research, qualitative, exploratory, and documentary in nature, analyzed 29 dissertations approved between 2016 and 2023 from MNPEF centers in the South and Southeast regions of Brazil, seeking to understand the possibilities emerging from teaching proposals that adopt an interdisciplinary approach between physics and art. Based on the theoretical framework on interdisciplinarity, two analytical categories were established: instrumental use of art and interdisciplinary integration. The analysis of the materials revealed that the incorporation of art into Physics teaching occurs, for the most part, in a punctual manner, serving as a supportive didactic resource. However, more in-depth proposals for articulating knowledge were also identified, capable of fostering more creative, critical, and contextualized educational experiences. The most frequently used artistic expressions were theater and comic strips. The findings indicate that the relationship between Physics and Art can significantly contribute to making teaching more engaging, meaningful, and connected to students’ realities, provided it is approached intentionally and reflectively. The study reinforces the importance of interdisciplinarity as a strategy to overcome curricular fragmentation and as a means for the holistic development of learners.
Physics and Art: an analysis of dissertations and products from the National Professional Master's Program in Physics Teaching
Keywords: Ensino de física; Física e arte; MNPEF; Interdisciplinaridade; Physics teaching; Physics and art; Interdisciplinarity; CIENCIAS HUMANAS::EDUCACAO::ENSINO-APRENDIZAGEM